Meningkatkan Omzet Wisata Air Sodong Desa Ligarmukti Kecamatam Klapanunggal Kabupaten Bogor melalui transformasi Sarana Prasarana dan Sumber Daya Manusia - Markonah, Markonah; umar, Haryono; AR, Hikmah; Esti Riwayati, Hedwigis (Jurnal Abdimas Perbanas, 2025)
This Community Service aims to increase the turnover of the Sodong water tourism in Ligarmukti Village, Klapanunggal District, Bogor Regency through the transformation of infrastructure and human resources by solving existing problems, including: poorly maintained and inadequate facilities and infrastructure for the Sodong water tourism in Ligarmukti, Bogor, namely: road access, parking facilities, bathroom and toilet facilities, rest areas, rest areas such as benches or gazebos around the tourist location are very limited and inadequate, cleanliness and waste management: lighting in the tourist area, minimal lighting, tour guide facilities and information. Overall, the condition of the facilities and infrastructure at the Sodong Ligarmukti water tourism is currently far from adequate and requires serious attention from the management and local government. The solutions will be resolved by: Carrying out a complete renovation of the Sodong Ligarmukti Bogor water tourism infrastructure in accordance with existing problems, Preparing a place to sell MSMEs (tenants' tents). With comprehensive and well-planned renovations, the water tourism area in Sodong Ligarmukti can become a more attractive and comfortable destination, and support local economic growth through the tourism sector.